2018
DOI: 10.1242/jcs.217406
|View full text |Cite
|
Sign up to set email alerts
|

Histone arginine methylation by Prmt5 is required for lung branching morphogenesis through repression of BMP signaling

Abstract: Branching morphogenesis is essential for the successful development of a functional lung to accomplish its gas exchange function. Although many studies have highlighted requirements for the bone morphogenetic protein (BMP) signaling pathway during branching morphogenesis, little is known about how BMP signaling is regulated. Here, we report that the protein arginine methyltransferase 5 (Prmt5) and symmetric dimethylation at histone H4 arginine 3 (H4R3sme2) directly associate with chromatin of to suppress its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 83 publications
4
22
0
Order By: Relevance
“…Consistent with previous observations in Prmt5-deficient limb (Norrie et al, 2016) and lung epithelium (Li et al, 2018) in mouse, we also observed increased ectopic Bmp4 signal in the growth plate of Col2Cre;Prmt5 f/f mutant IVDs at P10 that was not present in controls (Supplemental Fig. 6B, B').…”
Section: Prmt5 Regulates Bmp4 Expression In the Spinesupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous observations in Prmt5-deficient limb (Norrie et al, 2016) and lung epithelium (Li et al, 2018) in mouse, we also observed increased ectopic Bmp4 signal in the growth plate of Col2Cre;Prmt5 f/f mutant IVDs at P10 that was not present in controls (Supplemental Fig. 6B, B').…”
Section: Prmt5 Regulates Bmp4 Expression In the Spinesupporting
confidence: 92%
“…Loss of Prmt5 in limb bud and lung tissue induces ectopic, elevated Bmp4 expression which is accompanied by increased apoptosis in these tissues (Li et al, 2018;Norrie et al, 2016).…”
Section: Prmt5 Regulates Bmp4 Expression In the Spinementioning
confidence: 99%
See 1 more Smart Citation
“…The BMP family members play key roles in lung development and homeostasis . The signal transduction cascade is initiated when BMPs bind to BMP receptor I (BMPRI) and II (BMPRII), which are serine/threonine kinases .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The BMP family members play key roles in lung development and homeostasis. 4,[15][16][17][18][19] The signal transduction cascade is initiated when BMPs bind to BMP receptor I (BMPRI) and II (BMPRII), which are serine/threonine kinases. 20 The constitutively active BMPRII then phosphorylates and activates BMPRI, which in turn phosphorylates Smad 1/5/8.…”
mentioning
confidence: 99%